Konsep Ta’dib dalam Filsafat Pendidikan Syed Muhammad Naquib Al-Attas dan Relevansinya terhadap Krisis Adab Modern - Neni Hariyani Hairunnisa; Dayu Sumantoro; Siti Maryam; Siti Mahmudah Noorhayati (Educational Research Center, 2026)
This study aims to analyze the concept of ta’dīb in the philosophy of education proposed by Syed Muhammad Naquib Al-Attas and its relevance to the crisis of adab in modern education. The crisis of modern education is not merely related to technical-pedagogical issues but is rooted in epistemological and ontological problems resulting from the dominance of secular, positivistic, and utilitarian paradigms that separate knowledge from spiritual and moral values. This research employs a qualitative method with a library research approach. Primary data were obtained from the works of Syed Muhammad Naquib Al-Attas, particularly Islam and Secularism and The Concept of Education in Islam, while secondary data were collected from relevant books, journals, and scholarly articles. Data were analyzed using a descriptive-analytical method with philosophical and hermeneutical approaches to understand the epistemological, ontological, and axiological dimensions of the concept of ta’dīb. The findings reveal that ta’dīb represents an integrative and holistic concept of Islamic education, positioning adab as the core of education in shaping a civilized human being (insān ādabī). This concept emphasizes not only the acquisition of knowledge but also the development of moral character, spirituality, and ontological awareness in relation to God, humanity, and nature. Furthermore, ta’dīb demonstrates strong relevance in addressing the problems of secularization, the dichotomy of knowledge, and moral degradation in modern education through the integration of knowledge and values within the framework of tawḥīd. Therefore, ta’dīb can be regarded as a relevant and transformative paradigm of Islamic education in responding to the crisis of adab in the modern era.